Resistance induction efficiency of silicon dioxide against Meloidogyne incognita in tomato - Junior, Edilson Marques; Rosas, Jorge Tadeu Fim; Damascena, Alixelhe Pacheco; Silva, Matheus Alves; Camara, Guilherme de Resende; Gonçalves, Angelo Oliveira; Moraes, Willian Bucker (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
The tomato root-knot nematode is one of the main phytosanitary problems in crops. Chemical control is the phytosanitary method most used by farmers, and the study of alternative management of phytonematodes is crucial. The objective of this study was to evaluate the effect of silicon dioxide (SiO2) on the initial development of tomato plants, as well as to determine the best dose of SiO2 for inducing resistance to parasitism by M. incognita. This experiment was set up under a completely randomized design with ten treatments and five replicates in a 5×2 factorial arrangement consisting of five concentrations of SiO2 (0, 0.15, 0.3, 0.45 and 0.6 g dm-³ of soil) with the presence and absence of M. incognita, under greenhouse conditions. The following variables were evaluated: plant height; number of leaves; fresh and dry weight of shoot; percentage of shoot dry matter; root fresh weight; number of galls; final population of nematodes; and population per gram of root. The M. incognita infection affected plant height, number of leaves and shoot fresh weight, while the application of SiO2 negatively affected the formation of galls in the roots of the inoculated plants and the population per gram of root, reducing the final population of nematodes in the root system. SiO2 also provided greater development in the tomato plants, with a significant effect on plant height. The ideal dose was 0.34 g dm-3 of SiO2.